APPLICATION OF 5D INTERPOLATION ON MULTIAZIMUTH SEISMIK DATA PROCESSING FOR RESERVOIR GEOMECHANICS ANALYSIS - (NIM: 22315303), SUHERMAN
An over pressure was observed in 2500-4500 ft. depth of thick shale dominated lithology of Gumai formation during exploration well drilling in 1989 in South Sumatra basin. This phenomenon was followed by a wet saturated gas flowing from the top of over pressure zone in 2500 ft. Meanwhile in primary target zone in sand stones of Talang Akar formation an indication of oil was found but it couldn’t flow during the test because the main target was low permeability reservoir. It’s become a huge question because the reservoir has a good porosity around 20%. By knowing that, the development of this field should consider the over pressure and low permeability reservoir issues. An accurate pore pressure prediction is the key to analyze in situ stress. It can be used to estimates the magnitude of principle stresses in reservoir accurately. Furthermore, the orientation of principle stresses is very important to design both casing and well trajectory, analyze wellbore stability, estimate a safe mud weight and etc. But there is a lack of supporting data to analyze the orientation of principle stresses so 3D seismik data processing with five dimensional interpolation need to be done using Matching Pursuit Fourier Interpolation (MPFI) to enrich and widen its azimuth content. This 5D interpolated data is consequently processed as multi azimuth seismik data processing. The final result of this process is the multi azimuth velocity cube which is used to estimates pore pressure azimuthally using Eaton method approach. The predicted pressure is used to estimates not only the magnitude but also the orientation of in situ stresses. The final result are the magnitude and orientation of in situ stresses which is very accurate that can be used to develop the field.